2013
DOI: 10.1152/japplphysiol.00241.2012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of overweight on the active and the passive fraction of the plantar flexors series elastic component in prepubertal children

Abstract: The influence of overweight, as a precursor to obesity, was analyzed on the elastic properties of the triceps surae. Based on body mass index (BMI), children (9 years ± 4 mo) were classified as control (CON; n = 23; BMI -1SD>Z score<1SD) or overweight (OW; n = 21, BMI 1SD>Z score<3SD) with regard to reference data from the World Health Organization. Musculotendinous (MT) stiffness of the series elastic component (SEC) was determined using quick-release tests to obtain 1) the MT stiffness index from the slope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The statistical difference observed for the first 5-ms window should be considered with caution because the contribution was quantified for very small shortenings (Ͻ2-3 mm) of the tissues. The technique used here may be compared with the ␣-method (47) that has recently been adapted in vivo to estimate the stiffness of the active and passive part of the SEE of plantar flexors (9,17,19,44,58). This last method is mainly indirect because it calculates the stiffness of each part of the SEEs on the basis of only mechanical data (joint angle and external torque) and a model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical difference observed for the first 5-ms window should be considered with caution because the contribution was quantified for very small shortenings (Ͻ2-3 mm) of the tissues. The technique used here may be compared with the ␣-method (47) that has recently been adapted in vivo to estimate the stiffness of the active and passive part of the SEE of plantar flexors (9,17,19,44,58). This last method is mainly indirect because it calculates the stiffness of each part of the SEEs on the basis of only mechanical data (joint angle and external torque) and a model.…”
Section: Discussionmentioning
confidence: 99%
“…To measure its compliance in humans, classical methods were adapted from isolated muscle techniques such as quick-release (QR), controlled-release, or short-range stretching methods. For instance, numerous studies have used QR to investigate changes in musculotendinous stiffness induced by training programs (26,50), immobilization (43) or neuromuscular diseases (10,11), or to compare musculotendinous stiffness between different populations (41,44,52,53). This QR method consists of a sudden and fast release of the isometrically contracted muscle, as a "catapult-like" movement, using a specific ergometer (42,59).…”
Section: Farcy S Nordez a Dorel S Hauraix H Portero P Rabita Gmentioning
confidence: 99%
“…On the other hand, some differences have been reported between overweight/obese children and normal weight children in several studies. Lambertz et al [15] measured strength of triceps surae muscle using electromyography and reported an increased strength in obese children compared to normal weight children. Ervin et al [16] assessed muscle strength by observing children during a structured exercise program and they reported decreased performance in obese children in weight-bearing movements.…”
Section: Discussionmentioning
confidence: 99%
“…During physical activity, muscle cells must maintain tissue integrity while still exerting forces on their surrounding environment. On short timescales, muscles have an intrinsic stiffness that resists deformation, but also can isometrically contract to stiffen if needed [71]. Activity triggers long-term gene expression [72], allowing cells to adapt by growing bigger and changing their contractile ability in anticipation of future activity.…”
Section: Discussion: Sensing and Sorting Mechanical Signalsmentioning
confidence: 99%